Strategi Kepemimpinan Kepala Madrasah dalam Meningkatkan Kinerja dan Kedisiplinan Guru, (Studi Kasus di Madrasah Tsanawiyah (MTs) Al-Ikhlas Jambar Kuningan) - Waridin; Muslihun Muslihun; Ashari Ashari (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study uses a qualitative descriptive approach. Data analysis was conducted through qualitative descriptive methods. The results of the study indicate that mature leadership strategy planning, implementation with a participatory approach, and strict supervision can improve teacher performance and discipline. Programs that have been implemented, such as supervision, development of lesson plans, MGMP, IT deepening, fingerprint attendance, strengthening character education, and providing rewards and sanctions, have succeeded in creating a better and more conducive educational environment. The supporting factors for improving performance and discipline include visionary leadership, effective communication, resource support, collaborative work culture, consistent rule enforcement, and reward systems. Meanwhile, obstacles faced include lack of resources, minimal training, resistance to change, less supportive organizational culture, and administrative problems. Efforts to overcome these obstacles include increasing resources, developing continuous training, effective change management, improving organizational culture, and administrative reform.